Kinorhesis: A physiological principle of transformation that is complementary with homeostatic stability - Horseman, Nelson D. (Frontiers in Physiology, 2025)
Since being articulated by Claude Bernard, and ultimately named by Walter Cannon, the theory of Homeostasis has been a conceptual and practical bedrock of physiology and medicine. Homeostasis addresses the idea that internal stability is a requirement for survival and proper functioning of organisms. A great variety of transformative changes associated with development and reproduction are not addressed by homeostasis. Two familiar examples of non-homeostatic transformative processes are metamorphosis and childbirth. In a previous paper the name “kinorhesis” was proposed for a physiological principle encompassing the processes that account for episodes of transformative changes during reproduction, growth, and development. Like changes brought about by natural selection, kinorhetic transformations can have profound effects on the fitness of the organism in new or changing environments. But unlike evolutionary changes, kinorhesis takes place within the lifetime of the individual rather than across generations. Kinorhetic transformative changes exist alongside homeostasis such that the physiology of kinorhesis articulates with that of homeostasis. In most instances homeostasis and kinorhesis exist cooperatively, but sometimes they come into conflict. This paper will elaborate the new theoretical framework of kinorhesis using examples from across the biological Kingdoms, and describing the types of physiological mechanisms that distinguish homeostasis and kinorhesis. Physiological regulatory processes that are responsible for homeostasis and kinorhesis include compartmentation, negative feedback (normalizing reflexes), positive feedback (amplifying reflexes), and sequential controls. Homeostasis and Kinorhesis set boundaries on processes that provide stability and transformation to physiology, and they provide an heuristic framework for discovery and education. Kinorhesis employs the full scope of physiology from cellular level functions through organ systems, behaviors, and morphological changes. All aspects of homeostasis and kinorhesis are consistent with conventional theories and processes of Darwinian evolution.